Annexin A2 and Kidney Diseases - Lin, Ling; Hu, Kebin (Frontiers in Cell and Developmental Biology, 2022)
Annexin A2 is a Ca2+- and phospholipid-binding protein which is widely expressed in various types of cells and tissues. As a multifunctional molecule, annexin A2 is found to be involved in diverse cell functions and processes, such as cell exocytosis, endocytosis, migration and proliferation. As a receptor of plasminogen and tissue plasminogen activator, annexin A2 promotes plasmin generation and regulates the homeostasis of blood coagulation, fibrinolysis and matrix degradation. As an antigen expressed on cell membranes, annexin A2 initiates local inflammation and damage through binding to auto-antibodies. Annexin A2 also mediates multiple signaling pathways induced by various growth factors and oxidative stress. Aberrant expression of annexin A2 has been found in numerous kidney diseases. Annexin A2 has been shown to act as a co-receptor of integrin CD11b mediating NF-kB-dependent kidney inflammation, which is further amplified through annexin A2/NF-kB-triggered macrophage M2 to M1 phenotypic change. It also modulates podocyte cytoskeleton rearrangement through Cdc42 and Rac1/2/3 Rho pathway causing proteinuria. Thus, annexin A2 is implicated in the pathogenesis and progression of various kidney diseases. In this review, we focus on the current understanding of the role of annexin A2 in kidney diseases.